Industrial development survey - United Nations Industrial Development Organization (New York : United Nations, 1969)
This survey is the third in a series of industrial development surveys and is prepared in response to Economic and Social Council Resolution 1030 (XXXVH) requesting the Secretary-General to arrange for the preparation of periodic industrial development surveys, and in response to General Assembly Resolution 2152 (XXI) and Resolution 1 (I) adopted by the Industrial Development Board at its first session.
"United Nations publication. Sales no. E.68.II.B.18."
"Issued in 1967 as a document (ID/CONF.1/46) for the International Symposium on Industrial Development held in Athens, 29 November-20 December 1967."
Includes bibliographical footnotes.
lje 24/01/2018
Ref.
Keywords: Industries; Manufactures; Industrialization